The Principle of Fault In Absolute Responsibility For Environmental Crimes (Study of Decision Number 107/PDT.G/Lh/2019/PN JMB) - Fitria Wildasari; Tongat (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The environment holds an important position in the Indonesian legal system as stipulated in Article 28H paragraph (1) and Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia, which guarantees the right to a good and healthy environment. However, the increasing number of corporate activities that cause environmental pollution and damage raises fundamental issues related to criminal liability. Classical criminal law adheres to the principle of fault (mens rea), namely that a person can only be punished if they have intent (dolus) or negligence (culpa). The application of this principle becomes problematic when the perpetrator is a corporation that does not have an inner will like humans. To address this, Law Number 32 of 2009 concerning Environmental Protection and Management introduced the principle of strict liability, which allows for criminal punishment without proving the element of fault if environmental pollution or damage is proven to have occurred. This study analyzes the application of the principle of fault and the principle of strict liability in the Jambi District Court Decision Number 107/Pdt.G/LH/2019/PN Jmb using a juridical-normative method with a statutory and case approach. The study's findings indicate that the application of strict liability in the decision reflects a paradigm shift in environmental criminal law from a fault-based model to a system of accountability oriented toward ecological protection. While this principle strengthens the victim's position and the effectiveness of environmental law, it has also generated debate because it potentially undermines the principle of geen straf zonder schuld (no crime without fault).